Efficient Eradication of Mature Pseudomonas aeruginosa Biofilm via Controlled Delivery of Nitric Oxide Combined with Antimicrobial Peptide and Antibiotics - Ren, Hang; Wu, Jianfeng; Colletta, Alessandro; Meyerhoff, Mark E.; Xi, Chuanwu (Frontiers in Microbiology, 2016)
Fast eradication of mature biofilms is the ‘holy grail’ in the clinical management of device-related infections. Endogenous nitric oxide (NO) produced by macrophages plays an important role in host defense against intracellular pathogens, and NO is a promising agent in preventing biofilms formation in vitro. However, the rate of delivery of NO by various NO donors (e.g., diazeniumdiolates, S-nitrosothiols, etc.) is difficult to control, which hinders fundamental studies aimed at understanding the role of NO in biofilm control. In this study, by using a novel precisely controlled electrochemical NO releasing catheter device, we examine the effect of physiological levels of NO on eradicating mature Pseudomonas aeruginosa biofilm (7 d), as well as the potential application of the combination of NO with antimicrobial agents. It is shown that physiological levels of NO exhibit mixed effects of killing bacteria and dispersing ambient biofilm. The overall biofilm-eradicating effect of NO is quite efficient in a dose-dependent manner over a 3 h period of NO treatment. Moreover, NO also greatly enhances the efficacy of antimicrobial agents, including human beta-defensin 2 (BD-2) and several antibiotics, in eradicating biofilm and its detached cells, which otherwise exhibited high recalcitrance to these antimicrobial agents. The electrochemical NO release technology offers a powerful tool in evaluating the role of NO in biofilm control as well as a promising approach when combined with antimicrobial agents to treat biofilm-associated infections in hospital settings, especially infections resulting from intravascular catheters.